Posterior Spinal Fusion in a Scoliotic Patient With Congenital Heart Block Treated With Pacemaker: An Intraoperative Technical Difficulty - Wong, Tat Seng; Abu Bakar, Jaseemuddeen; Chee, Kok Han; Hasan, Mohd Shahnaz; Chung, Weng Hong; Chiu, Chee Kidd; Chan, Chris Yin Wei; Kwan, Mun Keong (Lippincott, Williams & Wilkins, 2019)
STUDY DESIGN: Case report. OBJECTIVE: To describe the technical difficulties on performing posterior spinal fusion (PSF) on a pacemaker-dependent patient with complete congenital heart block and right thoracic scoliosis. SUMMARY OF BACKGROUND DATA: Congenital complete heart block requires pacemaker implantation at birth through thoracotomy, which can result in scoliosis. Corrective surgery in this patient was challenging. Height gain after corrective surgery may potentially cause lead dislodgement. The usage of monopolar electrocautery may interfere with the function of the implanted cardiac device. METHODS: A 17-year-old boy was referred to our institution for the treatment of right thoracic scoliosis of 70°. He had underlying complete congenital heart block secondary to maternal systemic lupus erythematosus. Pacemaker was implanted through thoracotomy since birth and later changed for four times. PSF was performed by two attending surgeons with a temporary pacing inserted before the surgery. The monopolar electrocautery device was used throughout the surgery. RESULTS: The PSF was successfully performed without any technical issues and complications. Postoperatively, his permanent pacemaker was functioning normally. Three days later, he was recovering well and was discharged home from hospital. CONCLUSION: This case indicates that PSF can be performed successfully with thoughtful anticipation of technical difficulties on a pacemaker-dependent patient with underlying congenital heart block.5.